Moderate Dose Irradiation Induces DNA Damage and Impairments of Barrier and Host Defense in Nasal Epithelial Cells in vitro - Yang Y; Liu J; Liu Y; Ong HH; ChenQ; Chen CB; Thong M; Xu X; Zhou S; Qiu Q; Wang DY (Dove Medical Press, 2022)
Yue-Ying Yang,1,2,* Jing Liu,2,* Yi-Tong Liu,3,4 Hsiao-Hui Ong,2 Qian-Min Chen,2,4 Ce-Belle Chen,5 Mark Thong,6 Xinni Xu,6 Sui-Zi Zhou,3,4 Qian-Hui Qiu,3,4 De-Yun Wang2 1Department of Otolaryngology-Head and Neck Surgery, Zhujiang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 2Department of Otolaryngology, Infectious Diseases Translational Research Programme, Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 3Department of Otolaryngology-Head and Neck Surgery, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, People's Republic of China; 4The Second School of Clinical Medicine, Southern Medical University, Guangzhou, People's Republic of China; 5Centre for Ion Beam Applications, Department of Physics, National University of Singapore, Singapore; 6Department of Otolaryngology-Head and Neck Surgery, National University Hospital, National University Health System, Singapore*These authors contributed equally to this workCorrespondence: Qian-Hui Qiu, Department of Otolaryngology-Head and Neck Surgery, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, No. 106 Zhongshan Road II, Guangzhou, 510080, People's Republic of China, Tel +86 20 83827812, Email qiuqianhui@hotmail.com De-Yun Wang, Department of Otolaryngology, Infectious Diseases Translational Research Programme, Yong Loo Lin School of Medicine, NUHS Tower Block, 1E Kent Ridge Road, 119228, Singapore, Tel + 65 6772 5373/5370/5371, Fax +65 6775 3820, Email entwdy@nus.edu.sgPurpose: Radiotherapy (RT) is the mainstay treatment for head and neck cancers. However, chronic and recurrent upper respiratory tract infections and inflammation have been commonly reported in patients post-RT. The underlying mechanisms remain poorly understood.Method and Materials: We used a well-established model of human nasal epithelial cells (hNECs) that forms a pseudostratified layer in the air-liquid interface (ALI) and exposed it to single or repeated moderate dose γ-irradiation (1Gy). We assessed the DNA damage and evaluated the biological properties of hNECs at different time points post-RT. Further, we explored the host immunity alterations in irradiated hNECs with polyinosinic-polycytidylic acid sodium salt (poly [I:C]) and lipopolysaccharides (LPS).Results: IR induced DNA double strand breaks (DSBs) and triggered DNA damage response in hNECs. Repeated IR significantly reduced basal cell proliferation with low expression of p63/KRT5 and Ki67, induced cilia loss and inhibited mucus secretion. In addition, IR decreased ZO-1 expression and caused a significant decline in the transepithelial electrical resistance (TEER). Moreover, hyperreactive response against pathogen invasion and disrupted epithelial host defense can be observed in hNECs exposed to repeated IR.Conclusion: Our study suggests that IR induced prolonged structural and functional impairments of hNECs may contribute to patients post-RT with increased risk of developing chronic and recurrent upper respiratory tract infection and inflammation.Keywords: human nasal epithelial cells, irradiation, DNA double strand breaks, epithelial barrier, host defense